Dietary phosphatidylcholine supplementation attenuates inflammatory mucosal damage in a rat model of experimental colitis - Kovács Tamás (SHOCK, 2012)
This study was designed to follow the time course of inflammatory activation in a rodent model of 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis. We hypothesized that oral phosphatidylcholine (PC) pretreatment regimens may influence leukocyte-mediated microcirculatory reactions in this condition. In series I, Wistar rats were monitored 1 day after colitis induction (n = 24), and in series II (n = 24) on day 6 following a TNBS enema. The PC-pretreated animals received a 2% PC-enriched diet for 6 days before the TNBS enema (series I), or for 3 days before and 3 days after TNBS treatment (series II). The macrohemodynamics, serosal microcirculation (visualized by intravital videomicroscopy), colonic xanthine oxidoreductase, myeloperoxidase and nitric oxide end products, and changes in proinflammatory cytokine levels in plasma were measured. The mucosal structural injury was monitored in vivo by means of confocal laser scanning endomicroscopy. The TNBS enema induced a systemic hyperdynamic circulatory reaction with increased serosal capillary blood flow and significantly elevated colonic inflammatory enzyme activities, levels of nitric oxide production, and cytokine concentrations. Acute colitis caused disruption of the capillary network, whereas the morphologic damage was less severe in series II. The PC pretreatment protocols led to significant decreases in the serosal hyperemic reaction, the cytokine levels, and the inflammatory enzyme activities. The objective signs of tissue damage were reduced in both series, and the number of mucus-producing goblet cells in the resolving phase of colitis was increased. Dietary PC efficiently decreases the cytokine-mediated progression of inflammatory events and preserves the microvascular structure in the large intestine. © 2012 by the Shock Society.